Evaluasi Program Literasi Al-Qur’an di MTsN 2 Kota Palangka Raya - Beti Setiawati; Zainap Hartati; Nurul Hikmah (Kamaya: Jurnal Ilmu Agama, 2025)
The purpose of this study is to evaluate the reading and memorizing Al-Qur'an program at MTsN 2 Palangka Raya city by using the CIPP (Context, Input, Process, and Product) assessment model. The research method used in this study used a qualitative approach. The data collection techniques used are observation, interview, and documentation. The results of the research at the Contex stage show that with the help of a religious madrasah environment and adequate resources, this program was established to answer the needs of students who are not yet fluent in reading the Qur'an and to familiarize students with reading the Qur'an. In the Input aspect, the availability of competent educators and supporting infrastructure is found, although there is no special allocation of funds. The Process aspect shows the structured and routine implementation of the program, although there are still discipline constraints on some students. Meanwhile, the Product evaluation shows a significant increase in students' ability to read and memorize the Qur'an, as well as strengthening their self-confidence and spiritual closeness. Overall, the program is considered quite effective, but requires strengthening in the aspects of funding and fostering student discipline to achieve more optimal results.